Keratomycosis caused by Exserohilum rostratum - Noyal M Joseph; M Ashok Kumar; Selvaraj Stephen; Shailesh Kumar (Wolters Kluwer Medknow Publications, 2012)
We report a case of keratomycosis caused by Exserohilum rostratum. A 46-year-old farmer presented with history of pain, watery discharge and redness of the right eye for the past 2 weeks following trauma with vegetable matter. On ocular examination, a central corneal ulcer of about 8 mm with a greyish-white slough, feathery edges and diffuse corneal edema was seen in the right eye. KOH examination of corneal scrapings revealed thick, brown, branched, septate hyphae. Culture of corneal scrapings on Sabouraud dextrose agar showed velvety greenish-black colony with a black pigment on the reverse. The culture was identified as E. rostratum on the basis of microscopic morphology. The patient responded well to treatment with topical natamycin and oral itraconazole.